The influence of Limited-time Scarcity, Advertising, and E-wom on E-Impulse Buying towards virtual items in Genshin Impact - Andini Khairunnisa; Susi Evanita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study investigates the influence of Limited-time Scarcity, Advertising, and E-WOM (Electronic Word-of-Mouth) on E-Impulse buying behavior among players of Genshin Impact in the online community @paimonfess. Data from 400 respondents were collected through online questionnaires and analyzed using SmartPLS. The findings reveal that Limited-time Scarcity does not significantly and positively influence E-Impulse buying behavior. However, Advertising demonstrates a significant and positive impact on E-Impulse buying behavior, indicating that advertisements play a crucial role in encouraging impulse purchases among Genshin Impact players. Furthermore, E-WOM also shows a significant positive influence on E-Impulse buying behavior, highlighting the importance of word-of-mouth recommendations in shaping purchasing decisions within the online gaming community. These findings contribute to a deeper understanding of the factors driving E-Impulse buying behavior in the context of virtual item purchases in online gaming communities.